2017
DOI: 10.1159/000458462
|View full text |Cite
|
Sign up to set email alerts
|

Current Research on the Epidemiology, Pathogenesis, and Management of Necrotizing Enterocolitis

Abstract: Despite decades of research on necrotizing enterocolitis, we still do not fully understand the pathogenesis of the disease, or how to prevent or how to treat it. However, as a result of recent significant advances in the microbiology, molecular biology, and cell biology of the intestine of preterm infants and infants with necrotizing enterocolitis, there is some hope that research into this devastating disease will yield some important translation into effective prevention, more rapid diagnosis, and novel ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
77
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 113 publications
(87 citation statements)
references
References 91 publications
(98 reference statements)
2
77
0
1
Order By: Relevance
“…Although the aetiology is incompletely understood, it is thought to relate to aberrant intestinal mucosal colonisation by bacteria. Research efforts have focused on therapeutics designed to restore this balance to prevent NEC or minimise the severity once it has occurred (Denning et al 2017;Eaton et al 2017;Frost et al 2017). In 2014, a Cochrane review found that the use of probiotics reduced the occurrence of NEC (typical RR 0.35; 95% CI: 0.24 to 0.52, NNT 25) and death (typical RR 0.40; 95% CI 0.27 to 0.60, NNT 25) in premature infants with a birthweight of <1500 g (AlFaleh & Anabrees 2014).…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…Although the aetiology is incompletely understood, it is thought to relate to aberrant intestinal mucosal colonisation by bacteria. Research efforts have focused on therapeutics designed to restore this balance to prevent NEC or minimise the severity once it has occurred (Denning et al 2017;Eaton et al 2017;Frost et al 2017). In 2014, a Cochrane review found that the use of probiotics reduced the occurrence of NEC (typical RR 0.35; 95% CI: 0.24 to 0.52, NNT 25) and death (typical RR 0.40; 95% CI 0.27 to 0.60, NNT 25) in premature infants with a birthweight of <1500 g (AlFaleh & Anabrees 2014).…”
Section: Necrotising Enterocolitismentioning
confidence: 99%
“…These include necrotising enterocolitis (NEC), late-onset (hospital-acquired) infection, and associated slow growth and developmental faltering secondary to nutritional deficiency [1]. Late-onset infection affects about 20% and NEC occurs in about 5% of all very preterm infants [2, 3]. The attributable mortality can be in excess of 20%, especially for severe NEC and gram-negative bacterial, enterococcal or fungal infections.…”
Section: Introductionmentioning
confidence: 99%
“…The poor outcomes of these diseases have improved over the past decade due to significant advances in neonatal intensive care, especially for premature newborns, and the use of glucocorticoids and pulmonary surfactants. At present, the clinical treatment of premature diseases mainly includes auxiliary ventilation, drug therapy, supportive therapy and surgical treatment [9][10][11]. For example, the application of glucocorticoid in BPD can inhibit the occurrence of inflammatory reaction, reduce bronchial and pulmonary edema, promote the production of antioxidant enzymes and pulmonary surfactants in the lung, rapidly improve…”
Section: Introductionmentioning
confidence: 99%